(untitled) (Journal of Contemporary Educational Policies and Practices, 2025)
Along with the shutdown of schools, the coronavirus outbreak caused problems for implementing face-to-face classroom instruction. During this period, digital technologies offered a helpful substitute. This study investigated how students at Nguyen Tat Thanh University used digital technology following the coronavirus outbreak. The Technology Acceptance Model (TAM) and Constructivist Learning Theory were used to explain the findings. Thirty students were interviewed as part of the qualitative research design employed in the study. The results showed that, following the outbreak, students primarily used laptops and mobile phones to support their education. Additionally, it was discovered that these devices had the necessary software loaded, enabling communication between course instructors and students via Moodle, Zoom, WhatsApp, and YouTube. This study found that these tools were beneficial in helping students refine their typing, research, and information-seeking skills. However, drawbacks to using these devices included hardware failures, costly data bundles, and a lack of expertise with software operating protocols. When addressing these issues, the students used a variety of coping techniques. The study highlights several practical implications based on these conclusions.